2013
DOI: 10.1002/nau.22378
|View full text |Cite
|
Sign up to set email alerts
|

Factors implicated in pathogenesis of urinary tract infections in neurogenic bladders: some revered, few forgotten, others ignored

Abstract: In order to address the issue of urinary tract infection in patients with neurogenic bladders, multiple factors need to be looked into and corrected. Further research is required, especially in the area of compromised host defence mechanisms. An individualized approach, which attempts to optimize each factor is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
72
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(74 citation statements)
references
References 46 publications
0
72
0
2
Order By: Relevance
“…2 Risk factors for UTI in the NGB population are poorly understood; however, decreased bacterial washout due to inefficient voiding, vesicoureteral reflux, and altered hydrokinetics, as well as alterations in protective flora or the urothelium itself are potential contributors to increased rates of infection. 3 Non-sterile intermittent self-catheterization (ISC), unfortunately does violate the main defense mechanisms of the bladder by introducing bacteria into the system, but is the standard of care for bladder management in NGB with chronic retention, with advantages over indwelling catheters and no proven disadvantages when compared to sterile catheterization. 4 Strategies for preventing UTI in NGB patients on ISC are lacking in evidence.…”
Section: Introductionmentioning
confidence: 99%
“…2 Risk factors for UTI in the NGB population are poorly understood; however, decreased bacterial washout due to inefficient voiding, vesicoureteral reflux, and altered hydrokinetics, as well as alterations in protective flora or the urothelium itself are potential contributors to increased rates of infection. 3 Non-sterile intermittent self-catheterization (ISC), unfortunately does violate the main defense mechanisms of the bladder by introducing bacteria into the system, but is the standard of care for bladder management in NGB with chronic retention, with advantages over indwelling catheters and no proven disadvantages when compared to sterile catheterization. 4 Strategies for preventing UTI in NGB patients on ISC are lacking in evidence.…”
Section: Introductionmentioning
confidence: 99%
“…Immunological impairment has also been postulated, with studies demonstrating deficient mucosal immunity, impaired NK cell, B and T cell function, and defective urothelium that may result in absent apoptosis in response to intercellular signaling (9-11). Bladder ischemia from either over-distension or poor compliance may result in increased risk of infection as adequate blood flow is necessary for host defense mechanisms to function (12). From a mechanical standpoint, impaired washout also increases the risk of UTI.…”
Section: Background and Etiologymentioning
confidence: 99%
“…Firstly, they negate the protective effect of urethral length on prevention of UTI, specifically in the male. Secondly, they produce chronic inflammation, which may contribute to alterations in defense mechanisms such as the GAG layer (12). Finally, bacterial biofilms may form even in the absence of indwelling catheters (17).…”
Section: Background and Etiologymentioning
confidence: 99%
“…Evidence suggests that increased intravesical pressure results in bladder ischemia, which in turn may result in delayed or deficient immune response to pathogens. 10,11 Animal and human studies have found that increased intravesical pressure significantly reduces blood flow, in both the distended and empty bladder, suggesting global dysfunction. 12,13 Although most patients with NGB have abnormal urodynamic studies, many of these parameters can be mitigated successfully with medications or surgery.…”
Section: Bladder Dysfunctionmentioning
confidence: 99%
“…10 Animal studies have shown that 99.9% of bacteria injected into the bladder are removed by voiding. 14 Based on these studies, inefficient voiding with residual urine in theory predisposes to development of UTI.…”
Section: Urinary Stasis/increased Postvoid Residualmentioning
confidence: 99%